Interconnectedness of Financial Assets across the ASEAN-5 in Crisis Periods - Sumani, Sumani; Saadah, Siti (ETIKONOMI, 2026)
Research Originality: This study advances the financial connectedness literature by integrating a multi-asset (Bitcoin–stocks–sovereign bonds) and time-varying framework within the ASEAN-5 context. Unlike prior studies, this study uncovers a hierarchical and asymmetric spillover structure that evolves across market regimes, providing new evidence on cross-asset transmission channels in emerging markets. Research Objectives: The study aims to investigate the magnitude, direction, and dynamics of volatility spillovers among Bitcoin, stock, and bond markets, and to assess whether these interconnections change between normal and crisis periods. Research Method: Using daily data from January 2018 to April 2026, volatility is estimated through a GARCH model. A generalized VAR-based forecast error variance decomposition (G-FEVD), combined with a rolling window approach, is employed to capture both directional and time-varying spillovers. Empirical Results: The findings show a hierarchical spillover pattern: sovereign bonds act as net transmitters to Bitcoin, while Bitcoin transmits risk to stock markets. Spillover intensity increases significantly during crisis periods, peaking during COVID-19, indicating strong state-dependent connectedness. Cross-asset diversification weakens under market stress. Implications: These findings imply that financial stability cannot be assessed in isolation, as shocks propagate across asset classes in a structured, time-varying manner. This study underscores the importance of integrated cross-market surveillance frameworks that include digital assets alongside traditional markets. JEL Classification: G15, N25, H5